A Proposal of Logistic Services Innovation Strategy for a Mining Company - Cordova-Gonzalez, F; Sepulveda-Salas, J; Duran-San Martin, C (2012)
A logistic service innovation strategy for a mining company and their key suppliers is presented, using the win-win concept with the objective of improve its position, policies, strategic objectives and relationships between companies. The strategy allows increasing the business profitability, to diminish the operational costs and the times of negotiation and learning. The chain value of the productive process is analyzed and also the business strategies of each company in order to identify the key factors involved in the strategic alliance. Contracts negotiation between the company and its suppliers is examined by SWOT analysis, Pareto s ABC tool and expert knowledge of the process. The strategy is applied to a mining company and its key suppliers working in the modality of strategic long term alliances. © Universidad Alberto Hurtado, Facultad de Economía y Negocios.